EXPERIMENTAL EVALUATION OF BIOCHEMICAL MARKERS OF RAT BONE TISSUE AGAINST THE BACKGROUND OF MODELING CHRONIC EPILEPTIC ACTIVITY AND DENTAL CARIES - Shnaider, S.A.; Konovalov, M.F.; Ivchenko, N.A.; Yudina, O.O.; Novikova, Zh.O.; Tsevukh, L.B.; Khodorchuk, K.V. (World of Medicine and Biology, 2025)
This research is devoted to the modeling of chronic epileptic activity and dental caries with the aim of experimentally evaluating biochemical markers of bone tissues in rats. In the experiment, dental caries was reproduced by transferring the animals to Stephan’s cariesogenic diet, while epileptic activity was induced using the kindling and post-kindling models. The rats were divided into groups of six animals each. The results revealed a significant increase in acid phosphatase activity in the dental pulp of rats subjected to the cariesogenic diet and epileptic activity, indicative of tissue resorption processes in the teeth. The decrease in alkaline phosphatase activity signifies impaired mineralization processes in the hard dental tissues and suppression of odontoblast function. The combined influence of these factors exacerbated the pathological changes in the condition of the hard dental tissues, underscoring the need for specialized preventive measures in patients with epilepsy.